Bioprospecting and biotechnological insights into sweet-tasting proteins by microbial hosts―a review. Issue 4 (1st April 2022) - Bilal, Muhammad; Ji, Liyun; Xu, Shuo; Zhang, Yue; Iqbal, Hafiz M. N.; Cheng, Hairong
ABSTRACT: Owing to various undesirable health effects of sugar overconsumption, joint efforts are being made by industrial sectors and regulatory authorities to reduce sugar consumption practices, worldwide. Artificial sweeteners are considered potential substitutes in several products, e.g., sugar alcohols (polyols), high-fructose corn syrup, powdered drink mixes, and other beverages. Nevertheless, their long-standing health effects continue to be debatable. Consequently, growing interest has been shifted in producing non-caloric sweetenersfrom renewable resources to meet consumers' dietary requirements. Except for the lysozyme protein, various sweet proteins including thaumatin, mabinlin, brazzein, monellin, miraculin, pentadin, and curculin have been identified in tropical plants. Given the high cost and challenging extortion of natural resources, producing these sweet proteins using engineered microbial hosts, such as Yarrowia lipolytica, Pichia pastoris, Hansenula polymorpha, Candida boidinii, Arxula adeninivorans, Pichia methanolica, Saccharomyces cerevisiae, and Kluyveromyces lactis represents an appealing choice. Engineering techniques can be applied for large-scale biosynthesis of proteins, which can be used in biopharmaceutical, food, diagnostic, and medicine industries. Nevertheless, extensive work needs to be undertaken to address technical challenges in microbial production of sweet-tasting proteins in bulk. This review spotlights historical aspects, physicochemical properties (taste, safety, stability, solubility, and cost), and recombinant biosynthesis of sweet proteins. Moreover, future opportunities for process improvement based on metabolic engineering strategies are also discussed.